Assessment of selected food-service establishments patronized by UPV constituents - Sedonio, John Baylon (2011.)
The study aimed to determine if food-service establishments are indeed good venues for foodborne-disease outbreaks (Azana, 2006).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Food-service.